Odpowiedzi

2009-12-08T17:32:49+01:00
{2x+y=0/(-3)
2x+3y=2
{-6x-3y=0
2x+3y=2
-3x=2/:(-3)
x=- 2/3
{x=-2/3
2*(-2/3)+y=0
{x=-2/3
-4/3+y=0
{x=-2/3
y=4/3
2009-12-08T17:34:22+01:00
Nie mam pojęcia ;/ ale spróbuj tak /.//
2x+y=0
2x+3y=2
3y+2x=5yx
5y-2x=3y

x-4y=5
3x+2y=1
5x-1=4y
3x+2y=5
4y+1=5

y=5-2x
y=4-3x
5-3x=2x
5x+2=7
7x-4=3x
2009-12-08T17:39:55+01:00
2x + y = 0 / *(-1)
2x +3y=2

-2x -y=0
2x +3y=2

2y=2

y=1

2x+1=0
2x= -1

x = -1/2
y =1





x-4y=5
3x+2y=1 / *2

x-4y=5
6x+4y=2


7x=7
x=1


3+2y=1
2y=-2
y=-1
x=1



y=5-2x
y=4-3x


y+2x=5 /*(-1)
y+3x=4

-y-2x=-5
y+3x=4

x=-1

y-3=4
y=7
x=-1